Tobacco use and betel quid chewing among adults in Myanmar- estimates and social determinants from demographic and health survey, 2015-16 - Chandrashekhar T. Sreeramareddy; Saint Nway Aye; Sunil Pazhayanur Venkateswaran (BMC, 2021)
Abstract Background National-level prevalence of tobacco use and betel quid chewing, and associated socio-demographic factors were estimated using first-ever, Myanmar Demographic Health Survey, 2015-16. Methods Questions about tobacco smoking, smokeless tobacco use, and betel quid chewing were used to create outcome variables such as tobacco smoking, smokeless tobacco use, and 'dual use' (tobacco use and betel quid chewing). Sex-stratified weighted prevalence rates, distribution by socio-demographic factors were presented. Association of demographic factors with tobacco and/or betel quid chewing was assessed by multinomial logistic regression. Results Among men, prevalence (%) of tobacco use and betel quid chewing was 40.9 (95% CI 38.1, 42.1) and 58.9 (95% CI 56.3, 61.6) respectively. Among women tobacco use was 3.7 (95% CI 2.0, 4.3) and betel quid chewing 18.2 (95% CI 16.4, 20.0). Among men prevalence of either tobacco or betel quid and 'dual use' was 50.4 (95% CI 48.5, 52.3) and 25.0 (95% CI 23.1, 26.8) respectively, whereas among women the corresponding rates were 17.9 (95% CI 16.2, 19.6) and 2.0 (95% CI 1.6, 2.9). Smokeless tobacco use was low (< 5%) in both sexes. Tobacco use and/or betel quid chewing was associated with age, wealth, marital status, and occupation in both sexes. However, the effect sizes were much larger among women for wealth groups. People of older age and lower wealth had a higher odds of being a tobacco user and/or betel quid chewer. Conclusions In Myanmar, prevalence of both tobacco use and betel quid chewing was high particularly among men. Tobacco control interventions should be strictly implemented and 'dual use' of both tobacco and betel quid should also be urgently addressed.